If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(-6 + x) = -30 (-6 * 2 + x * 2) = -30 (-12 + 2x) = -30 Solving -12 + 2x = -30 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 2x = -30 + 12 Combine like terms: -12 + 12 = 0 0 + 2x = -30 + 12 2x = -30 + 12 Combine like terms: -30 + 12 = -18 2x = -18 Divide each side by '2'. x = -9 Simplifying x = -9
| 12/3=4/n | | 2x+4+5x-11=180 | | C/7=20/35 | | 32+5y= | | 20/35=c/7 | | 2x-3+6=x+1+1 | | 33y+28=25y-12 | | 114-6^2*9/(3*10-7*3)= | | 50x=20x+210 | | -6(x+1)=0 | | -19=k+21 | | -2d(d^3c^2-4dc^2+2d^2c)+c^2(dc^2-3d^4)=0 | | (2x+1)=(x-16) | | 36x^2+12x=13 | | 5a-3b+2a-7b= | | r^2-7r-8= | | 3x-2=4(x+1)+2x | | 2=-6+3 | | 91=c-(-12) | | 3x+15=x+10 | | -133=-14+52x-35x | | (2x+12)=(5x-7) | | y=20x^2+x-1 | | 4(3x+5)-6(3x-7)=10x+3(4x-7) | | 11x-132=144-x | | -2(v-6)=6v-12 | | 2x+5x+15=90 | | -2x-20=2(x-2) | | X(3x^2+4)+2(7x-3)=0 | | .66x-.16=.5x+.83 | | 5y-5=(2y+5)+(2y+5) | | 6(v-6)=-8v+34 |